Menemukan Cahaya: Peran Guru dalam Membamgun Semangat Belajar - Iwan Saputra; Sutarto Sutarto (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to explore the strategic role of teachers in building students' enthusiasm for learning amidst modern challenges, such as technological developments, the impact of the pandemic, and social change. The research methodology uses library research with content analysis to review relevant literature on learning strategies and student motivation. The results of the study indicate that the role of teachers as facilitators, motivators, inspirators, guides, and evaluators is very influential in increasing students' learning motivation. Innovative and adaptive teachers are able to create a fun, relevant, and interactive learning environment, so that students are more motivated to learn. This study highlights the importance of professional training for teachers and the integration of educational technology to overcome obstacles faced in the learning process.